The Influence of Price and Coffee Shop Atmosphere on Coffee Shop Consumer Satisfaction in Sampit City - Eko Cahyo Purnomo; Hari Susanto; Deky Prasetyo; Sylva Rulliansyah (International Journal of Science and Environment (IJSE), 2025)
This study aims to analyze the influence of price and atmosphere on consumer satisfaction at Coffee 1999 in Sampit City. The research method used is a quantitative approach with data collection through questionnaires to respondents who are Coffee 1999 customers. The data analysis technique uses multiple linear regression analysis with t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results of the study show that: (1) the price variable has a positive and significant effect on consumer satisfaction with a calculated t-value (3.655) > t-table (2.02809) and significance (0.001 < 0.05); (2) the atmosphere variable also has a significant effect on consumer satisfaction with a calculated t-value (2.337) > t-table (2.02809) and significance (0.025 < 0.05); and (3) the results of the simultaneous test show that price and atmosphere together have a significant effect on consumer satisfaction with an F-count value (31.152) > F-table (3.26) and significance (0.000 < 0.05). The R² value of 0.627 indicates that the two independent variables influence consumer satisfaction by 62.7%, while the remaining 37.3% is influenced by other variables. This study confirms that the implementation of the right pricing strategy and the creation of a comfortable café atmosphere are important factors in building and maintaining customer satisfaction.